Comparison of Two Different Morphological Methods to Study the Pronotum of Cimicidae: Bed Bugs, Bat Bugs, and Swallow Bugs - Dora M. Rajonhson; Chadchalerm Raksakoon; Anon Payakkapol; Sébastien Dujardin; Jean-Pierre Dujardin; Rutcharin Potiwat (Insects, 2022)
An infestation of a Cimicidae (Hemiptera: Cimicidae) member, especially the bed bug, can cause economic loss and impact health. A cost-effective and user-friendly method for identifying the infesting species will help with the early detection and control of infestations. A linear morphometric method is often used, but it requires the examination of many characters and a highly preserved specimen. We conducted a comparative morphometric study of the effectiveness of Cimicidae classification using a single organ, the pronotum, through outline-based and linear morphometric methods. Bat (Stricticimex parvus), human (Cimex hemipterus), and bird (Paracimex sp.) ectoparasites were subject of the study. With both methods, the properties of size and shape were compared and used separately to classify the specimens. Classification analyses of the two methods provided similar results, but more informative variables of size and shape were obtained with the outline-based approach. Size, as analyzed with the outline-based method, could detect sexual dimorphism, and produced better reclassification. The shape variables obtained from the linear measurements were strongly influenced by size variation, much more than the ones obtained from coordinates describing the pronotum contours. Our data suggest that the outline-based approach provides better characterization variables, thus we recommend them for a wider use in other Cimicidae family members.